Characterisation of elemental analysis, carbon sulphur analysis and impact test of stent manufacturing using medical grade ASTM F75 cobalt chromium (CoCrMo) by selective laser melting (SLM) technology - Omar, Mohd Asnawi; Baharudin, B. T. Hang Tuah; Sulaiman, S.; Ismail, Mohd Idris Shah; Omar, Mohd Afian (Taylor and Francis, 2021)
This paper explains and demonstrates the capabilities of metal additive manufacturing (MAM) technology in producing intricate stent structure with a customise design by using ASTM F75 cobalt chromium powder. The elemental analysis (EDX-SEM), carbon sulphur analysis and Impact Test are being develop and tested and thus exploring the potential area of MAM process for future proof stent manufacturing. By alternatively switching to MAM, the step of production can be minimised and thus customisation of stent can be carried out according to the patient’s need. The suggested model of the stent was taken from the third-party vendor and fabrication was carried out using EOSINT M280 metal printer with the aid of Materialise Magics 19.0 software for support generation.